2019
DOI: 10.1111/jocd.13194
|View full text |Cite
|
Sign up to set email alerts
|

Traffic‐derived air pollution compromises skin barrier function and stratum corneum redox status: A population study

Abstract: Background Since air pollution is only one of many environmental stressors that can affect skin, it has been challenging to identify skin appearance or functional features profoundly affected by chronic exposure to traffic‐derived air pollution. Aims The current population study focused on taxi drivers working in urban and rural areas in order to take advantage of difference in occupational exposure. Methods The skin conditions of 100 middle‐aged male taxi drivers from urban Shanghai and 66 from rural Chongmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Although it is reasonable to assume that the skin is one of the first organs to be affected by air pollution, our knowledge regarding the harmful effects of air pollution on skin physiology remains limited. It has been recently shown that air pollution, mainly PM, can penetrate the skin barrier and alter its redox status (2,3). Particulate matter induces oxidative stress, increases reactive oxygen species (ROS) production and secretion of pro-inflammatory cytokines, resulting in lipid peroxidation (LPO) and DNA damage.…”
mentioning
confidence: 99%
“…Although it is reasonable to assume that the skin is one of the first organs to be affected by air pollution, our knowledge regarding the harmful effects of air pollution on skin physiology remains limited. It has been recently shown that air pollution, mainly PM, can penetrate the skin barrier and alter its redox status (2,3). Particulate matter induces oxidative stress, increases reactive oxygen species (ROS) production and secretion of pro-inflammatory cytokines, resulting in lipid peroxidation (LPO) and DNA damage.…”
mentioning
confidence: 99%
“…Our previous report demonstrated that urbanization-related pollution stress significantly affected skin physiological properties, including skin indices like total antioxidant capacity, cholesterol levels, vitamin E (VE), and transepidermal water loss (TEWL), and the activities of stratum corneum tryptic enzyme (SCTE) and catalase ( 18 ). While there is evidence indicating that skin microbes may be involved in certain biochemical events related to cholesterol esterification ( 21 ), skin antioxidant defense ( 22 ), and epidermal proteolytic activity ( 23 ), the mediative role of microbes in driving skin biophysical and biochemical responses toward environmental stimuli remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-three, 11, and 2 years were the median value of the corresponding variables of age, years of working, and service life of the taxi. Detailed information on this clinical study was previously reported ( 18 ). In brief, exclusion criteria included daily alcohol drinking, skin diseases, regular medication with antihistamines or anti-inflammatory drugs, or having had facial cosmetic procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is reasonable to assume that the skin is one of the first organs to be affected by air pollution, our knowledge regarding the harmful effects of air pollution on skin physiology remains limited. It has been recently shown that air pollution, mainly particulate matter, can penetrate the skin barrier and alter its redox status [2,3]. PM induces oxidative stress, increases ROS production and secretion of pro-inflammatory cytokines, resulting in lipid peroxidation and DNA damage.…”
Section: Introductionmentioning
confidence: 99%